Study of the impedance transformation ratio of microwave rectifier for outphasing power recycling application - Defu Wang; Renato Negra (2015 IEEE Topical Conference on Power Amplifiers for Wireless and Radio Applications (PAWR), 2015)
This paper presents an analysis for the impedance transformation ratio of microwave rectifier, implemented as an energy recycling unit suitable for RF outphasing transmitters. The experimental demonstration is realised by two single-ended microwave rectifiers with different impedance transformation ratios to separately replace the power-wasting resistive load of an isolating combiner in a multilevel LINC system. The measurement results show that the implemented rectifier can improve the overall efficiency of the multilevel LINC system from original 39.5 % to 46.7 % and 44.9 % respectively, without affecting linearity.